2017
DOI: 10.12973/eurasia.2017.01239a
|View full text |Cite
|
Sign up to set email alerts
|

Pupils’ Attitudes toward Chemistry in Two Types of Czech Schools

Abstract: Chemistry is a school subject that is not viewed favorably among pupils. Before we can improve pupils' attitudes toward chemistry, it is important to find out the problem as to why the attitudes are relatively negative. The research was focused on Czech lower secondary and secondary grammar school pupils' attitudes to the subject of chemistry. Also, the difference between groups of variables (gender and grade) was examined. The sample size contained 931 Czech lower secondary and secondary grammar school pupils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 21 publications
2
17
0
1
Order By: Relevance
“…Similarly, another factor the grade level was disclosed in 9 studies out of the 36, seven of them clearly showed their positive effect (some with a statistically significant effect of p < 0.05 (Can, 2012;Can & Boz, 2012), a high statistical significant effect with p < 0.01 (Cheung, 2009a;Hofstein et al, 1977), and a very high statistical significant effect with p <0.001 (Heng & Karpudewan, 2015;Montes et al, 2018). Two studies showed no effect of grade level on students' attitudes towards chemistry (Akarsu & Kariper, 2013;Kubiatko et al, 2017). (Freedman, 1997) Students treated using laboratory instruction showed a higher score and a positive attitude (p˂0.01).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, another factor the grade level was disclosed in 9 studies out of the 36, seven of them clearly showed their positive effect (some with a statistically significant effect of p < 0.05 (Can, 2012;Can & Boz, 2012), a high statistical significant effect with p < 0.01 (Cheung, 2009a;Hofstein et al, 1977), and a very high statistical significant effect with p <0.001 (Heng & Karpudewan, 2015;Montes et al, 2018). Two studies showed no effect of grade level on students' attitudes towards chemistry (Akarsu & Kariper, 2013;Kubiatko et al, 2017). (Freedman, 1997) Students treated using laboratory instruction showed a higher score and a positive attitude (p˂0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Among the eleven factors, gender was tackled in 19 studies out of 36. Thirteen clearly showed their significant main effect (p < 0.05 (Can, 2012;Heng & Karpudewan, 2015;Kenar et al, 2015;Kubiatko et al, 2017;Menis, 1983), a highly significant effect with p<0.01 (Anwer et al, 2012) and others with a very high significant main effect of p < 0.001 (Cheung, 2009b;Heng & Karpudewan, 2015;Hofstein et al, 1977;Salta & Tzougraki, 2004). However, six studies showed no effect of gender on the attitude of students (Akcay et al, 2010;Inye, 2011;Montes et al, 2018;Najdi, 2018;Ngila & Makewa, 2014;Sakariyau et al, 2016), (p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations